A Conceptual Framework for Gamified Digital Product Passports - Christopoulos, Athanasios; Psarommatis, Foivos; Bourazeri, Aikaterini; Stylios, Chrysostomos (Switzerland, 2026)
Digital Product Passports came with the promise to bring about supply chain transparency. However, since their emergence, several adoption barriers have been identified primarily due to stakeholder disengagement and misaligned incentives. To this end, while regulatory mandates drive compliance, passive information repositories often fail to generate meaningful participation from suppliers and/or consumers. In consideration of this shortcoming, the present work proposes a Digital Product Passport framework enriched by gamification elements as a means of transforming transparency from burden to opportunity and individual motivations to collective transparency goals. In greater detail, the framework addresses supplier reluctance through competitive transparency scoring and value sharing mechanisms and further engages consumers through interactive product journey narratives and impact visualisation. The work contributes to the behavioural design research field by proposing an alternative framework that leverages intrinsic and extrinsic motivation in order to overcome traditional barriers to supply chain transparency. To contextualise these ideas, we provide illustrative scenarios demonstrating how gamification mechanisms could create self-reinforcing feedback loops between suppliers and consumers.